Cleaner Production Value Stream Mapping At A Chromium Plating Plant: A Case Study - Mohamad, Effendi; Salleh, Mohd Rizal; A Rahman, Muhamad Arfauz; Sulaiman, Mohd Amri; Ishak, Anuar; Teruaki, Ito (Inderscience Enterprises Ltd., 2019)
The conventional value stream mapping (VSM) processes could improve the performance of the three pillars, due to its sustainability, cost effective and many additional benefits. However, it does not take into consideration both the environmental and societal metrics at the same time. In this work, the ‘lean and environmental toolkits’ proposed by US Environmental Protection Agency (USEPA, 2007) and the Malaysian Green Industry Auditor Guidelines (2014), was synergised. The work conducted at SME chromium plating company in Malaysia embeds different measures using the cleaner production (CP) technology in the novel VSM technique, and known as cleaner production VSM (CPVSM). This may promote the production line sustainability. This embedded technology has been proved to be an efficient visualisation process for the lean practices and able to promote a sustainable development at the implemented levels. The CP process implementation could also be improved and the lean manufacturing (LM) sustainability can be promoted